2021
DOI: 10.1161/jaha.120.016998
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Ruptured and Unruptured Aneurysms Treatment in the United States in Post‐ISAT Era: A National Inpatient Sample Analysis

Abstract: Background The ISAT (International Subarachnoid Aneurysm Trial) has generated a paradigm shift towards endovascular treatment for intracranial aneurysms but remains unclear if this has led to a true reduction in the risk for aneurysmal subarachnoid hemorrhage (aSAH). We sought to study the association between the treatment burden of unruptured and ruptured aneurysms in the post‐ISAT era. Methods and Results Admissions data from the Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Although direct causality cannot be ascertained, they suggested that this decrease was the result of pre-emptive treatment of high-risk unruptured intracranial aneurysms. 16 This data showed the benefit of performing screening in selected individuals with a high risk for intracranial aneurysm. Regarding treatment modalities, since the publication of the International Subarachnoid Aneurysm Trial (ISAT), there has been an increase in the number of coiling procedures.…”
Section: Original Articlementioning
confidence: 75%
See 1 more Smart Citation
“…Although direct causality cannot be ascertained, they suggested that this decrease was the result of pre-emptive treatment of high-risk unruptured intracranial aneurysms. 16 This data showed the benefit of performing screening in selected individuals with a high risk for intracranial aneurysm. Regarding treatment modalities, since the publication of the International Subarachnoid Aneurysm Trial (ISAT), there has been an increase in the number of coiling procedures.…”
Section: Original Articlementioning
confidence: 75%
“…Studies from the United States of America and Korea reported that the number of coiling performed for either unruptured or ruptured intracranial aneurysm has increased substantially, overtaking clipping as the most performed procedure for treating aneurysm. 16,17 Our study has several limitations. The retrospective and single-center designs have an inherent risk of confounding bias.…”
Section: Original Articlementioning
confidence: 94%
“…In the United Kingdom, the overwhelming majority of aneurysms are clipped by subspecialist neurovascular surgeons but in an environment that has some important differences compared with the large United States centres that feature prominently in the literature. For example, resources are significantly more constrained with 50% lower healthcare expenditure per capita ( 43 ), it is much less common for neurovascular surgeons to be dual-trained, and the overall proportion of aneurysms treated endovascularly is higher ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the patients who were considered for treatment, endovascular (70%) or surgical (30%) treatment was used. 26…”
Section: Discussionmentioning
confidence: 99%